ON THE FUNCTIONS OF ELEMENTS OF ORAL SPEECH USED IN ARTISTIC SPEECH (Scientific journal of the Fergana State University, 2024)
This article discusses the functions of dialectisms used in the literary text and the purposes of their use. Also, there was talk about the expressive possibility and importance of dialectal units in the artistic text, as well as the specific aspects of the author's speech. The analysis method is used in the article. The linguistic evidence given to confirm the opinions in the article is taken from the poems of Farida Afro‘z.